Application of Ethical Sanctions for Abuse of Influence by Members of The Corruption Eradication Commission - Gengki Zulfikar, M Haidar Hanif; Hartoyo, Hartoyo; Astutik, Sri (Rechtsvinding, 2025)
The establishment of the Republic of Indonesia as a State of Law requires that all actions must be based on the Law, this is also done in the Corruption Law Enforcement institution which is regulated in Law Number 30 of 2002 concerning the Corruption Eradication Commission, although in its journey there are violations such as those committed by the deputy chairman of the Corruption Eradication Commission, namely brother NG, who has been sanctioned by the KPK Supervisory Board with moderate sanctions as stipulated in the Regulation of the Supervisory Board of the Corruption Eradication Commission of the Republic of Indonesia Number 3 of 2021 concerning Enforcement of the Code of Ethics and Code of Conduct of the Corruption Eradication Commission, but this does not reflect justice considering NG's position as KPK Leader. In this case, the problem formulation is used, namely 1) How is the application of ethical sanctions against abuse of influence by members of the Corruption Eradication Commission? 2) Can Ethical Sanctions be Used as a Foundation in Law Enforcement of Corruption Crimes? By using the Normative Juridical research method and 2 (two) Approach Methods, namely the statute approach, conceptual approach, several conclusions were drawn that the sanctions imposed on Ng as KPK Leader did not reflect justice and fulfill the theory of punishment, namely the deterrent effect, where NG should have been imposed with severe sanctions considering his position as KPK Leader